2017
DOI: 10.1186/s12883-017-0977-0
|View full text |Cite
|
Sign up to set email alerts
|

EEG dynamical correlates of focal and diffuse causes of coma

Abstract: BackgroundRapidly determining the causes of a depressed level of consciousness (DLOC) including coma is a common clinical challenge. Quantitative analysis of the electroencephalogram (EEG) has the potential to improve DLOC assessment by providing readily deployable, temporally detailed characterization of brain activity in such patients. While used commonly for seizure detection, EEG-based assessment of DLOC etiology is less well-established. As a first step towards etiological diagnosis, we sought to distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The most typical and probably mentioned (kernel-based) algorithm for classification is known as Support Vector Machine (SVM) (Boser et al, 1992; Vapnik, 1995, 1998). An example of its application for DOC analysis can be found in Engemann et al (2015), Chennu et al (2017), and Kafashan et al (2017). Different approaches are given in Wielek et al (2018) where standard scoring rules developed by American Academy of Sleep Medicine were applied.…”
Section: Resultsmentioning
confidence: 99%
“…The most typical and probably mentioned (kernel-based) algorithm for classification is known as Support Vector Machine (SVM) (Boser et al, 1992; Vapnik, 1995, 1998). An example of its application for DOC analysis can be found in Engemann et al (2015), Chennu et al (2017), and Kafashan et al (2017). Different approaches are given in Wielek et al (2018) where standard scoring rules developed by American Academy of Sleep Medicine were applied.…”
Section: Resultsmentioning
confidence: 99%
“…Scarpino et al [54] showed that specific EEG patterns were independent predictors of improved consciousness at discharge in UWS patients. Some studies showed that EEG provides accurate prognostic information in the early phase of coma [55][56][57]. Evoked potential examination plays an increasingly important role in predicting the rehabilitation and prognosis of patients with craniocerebral injury and disturbance of consciousness [58].…”
Section: Discussionmentioning
confidence: 99%
“…13,14,25,26 The support vector machine (SVM), a statistical machine learning algorithm, has been used in a wide range of biomedical applications, including automated seizure detection. 15,17,2729…”
mentioning
confidence: 99%